2018
DOI: 10.1002/jsfa.9205
|View full text |Cite
|
Sign up to set email alerts
|

Wines in contact with oak wood: the impact of the variety (Carménère and Cabernet Sauvignon), format (barrels, chips and staves), and aging time on the phenolic composition

Abstract: Extraction of phenolic compounds from oak wood during wine aging is closely related to the wood format, grape variety (Carménère or Cabernet Sauvignon), and aging time. The final effect of wood on wine would be related not just to the transference of polyphenols from wood, but also to structural modifications of grape polyphenols. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 33 publications
9
23
0
1
Order By: Relevance
“…From that moment, this parameter decreased in all the treatments, maintaining the initial differences until the end of the aging process (Figure 2a). These results coincide with those obtained by other authors [16,17]. Furthermore, a higher CI in micro-oxygenated wines was also observed by other authors [18,19], which could be due to an increase in the blue color by the contribution of pigments with ethyl bridges.…”
Section: Color Parameters Of Winesupporting
confidence: 93%
“…From that moment, this parameter decreased in all the treatments, maintaining the initial differences until the end of the aging process (Figure 2a). These results coincide with those obtained by other authors [16,17]. Furthermore, a higher CI in micro-oxygenated wines was also observed by other authors [18,19], which could be due to an increase in the blue color by the contribution of pigments with ethyl bridges.…”
Section: Color Parameters Of Winesupporting
confidence: 93%
“…These authors reported that a sensory analysis showed that the wines treated with Colombian oak presented more notes of smoked and less of coconut. Laqui‐Estaña et al . reported that Carmenère and Cabernet‐Sauvignon wines in contact with oak wood presented a high amount of caffeic acid, gallic acid, ellagic acid, and ellagitannins, whereas the wines in contact with staves were characterized by total phenols, vanillic acid, and higher color intensity.…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
“…143 These authors reported that a sensory analysis showed that the wines treated with Colombian oak presented more notes of smoked and less of coconut. Laqui-Estaña et al 144 reported that Carmenère and Cabernet-Sauvignon wines in contact with oak wood presented a high amount of caffeic acid, gallic acid, ellagic acid, and ellagitannins, whereas the wines in contact with staves were characterized by total phenols, vanillic acid, and higher color intensity. These authors also reported that the Carmenère and Cabernet-Sauvignon wines aged with chips presented a large amount of proanthocyanidin gallates, whereas the wines aged in barrels showed high ellagitannin and ethyl gallate content.…”
Section: Carmenèrementioning
confidence: 99%
“…Модель CIELab позволила исследовать колориметрические изменения сусла и виноматериалов на разных этапах производственного цикла, установить влияние различных технологических приемов (брожение, настаивание мезги, выдержка), микроорганизмов (дрожжи, молочнокислые бактерии), вспомогательных материалов на качество красных вин, а также оценить перспективность новых сортов винограда и роль региона произрастания винограда [62][63][64][65]. Установлена корреляционная зависимость между значением параметров цвета и содержанием фенольных веществ в вине [66].…”
Section: таблицаunclassified